Anxiety in cirrhosis: a prospective study on prevalence and development of a practical screening nomogram. Issue 5 (29th October 2021) - Dang, ThucNhi T.; Patel, Kinjal; Farhat, Kamal; Abraldes, Juan; Ma, Mang; Bailey, Robert J; Burak, Kelly W.; Mitchell, Nicholas; Tandon, Puneeta
Abstract : Objectives: The prevalence and effects of anxiety on health-related quality of life and clinical outcomes in cirrhosis are not well understood. This is increasingly relevant during COVID-19. Our aim was to use the Mini-International Neuropsychiatric Interview (MINI) to determine the prevalence of anxiety, its association with clinical outcomes in cirrhosis and to develop a rapid cirrhosis-specific anxiety screening nomogram. Methods: Adults with a diagnosis of cirrhosis were prospectively recruited as outpatients at three tertiary care hospitals across Alberta and followed for up to 6 months to determine the association with unplanned hospitalization/death. The Hospital Anxiety and Depression scale (HADS) was used as a screening tool as it is free of influence from somatic symptoms. Anxiety was diagnosed using the MINI. Results: Of 304 patients, 17% of patients had anxiety by the MINI and 32% by the HADS. Anxious patients had lower health-related quality of life as assessed by the chronic liver disease questionnaire ( P  < 0.001) and EuroQol Visual Analogue Scale ( P  < 0.001), and also had higher levels of frailty using the Clinical Frailty score ( P  = 0.004). Multivariable analysis revealed smoking and three HADS subcomponents as independent predictors of anxiety. These were used to develop a rapid screening nomogram. Conclusion: A formal diagnosis of anxiety was made in approximately one in five patients with cirrhosis, and it was associated with worse HrQoL and frailty. The use of a 4-question nonsomatic symptom-based nomogram requires validation but is promising as a rapid screen for anxiety in cirrhosis.